The Achievement Of Student Developmental Task Based On Type Of School - Tazkia Dini Azhara; Herman Nirwana; Syahniar Syahniar (Universitas Negeri Padang, 2020)
The objective of study is to describe the achievement of student developmental task based on the type of schools that are Senior High School and Islamic Boarding School. This study used quantitative methods with comparative descriptive approach. The samples in this study were amounted 429 students that consisted of 219 students of Public Senior High School 3 Padang Panjang, and 210 students of Islamic Boarding School of Sumatra Thawalib Parabek, Bukittinggi. The samples were selected by using the Proposional Random Sampling technique.The instrument used was Instrument of the Achievement of Student Developmental Task (IKTPS), with reliability of 0.925. In testing the differences between independent variable and dependent variable were analyzed by t-test. The findings of study showed there were differences of the achievement of student developmental task with different backgrounds between Senior High School and Islamic Boarding School, which is student in Senior High School have higher levels of their developmental task achievement than student in Islamic Boarding School.